Comprehensive Analysis on Physicochemical Properties and Characteristic Compounds of Insect-Infested Ziziphi Spinosae Semen - Bo Xu; Zhenying Liu; Yanzhen Shen; Yunxia Cheng; Pingping Song; Feifei Wang; Zhimao Chao (Metabolites)
Objectives: Ziziphi spinosae semen (ZSS), an edible and medicinal substance, was easily infested by Plodia interpunctella (P. interpunctella) during storage. However, there was no identification method for insect-infested ZSS based on its chemical composition. Therefore, the characteristic compounds in ZSS before and after being infested by P. interpunctella were discovered based on the comparison of volatile organic compounds (VOCs), untargeted metabolomics, and other quality characters. Methods: Color, total flavonoid content (TFC), and main active compound content were measured to explore the change of physicochemical properties in ZSS after being infested by P. interpunctella. Non-targeted metabolomic techniques, including ultra-performance liquid chromatography–mass spectrometry (UPLC-MS) and headspace solid-phase microextraction–gas chromatography–mass spectrometry (HS-SPME-GC-MS) were used to assess molecular-level alterations. Results: The color changed significantly. The TFC and main active compounds of spinosin, jujuboside A, jujuboside B, and betulinic acid were decreased significantly. A total of nine VOCs and twenty-one metabolites were screened out that could be used to identify whether ZSS was infested. And some metabolites, such as uric acid, gluconic acid, hypoxanthine, and xanthine, were discovered as characteristic compounds in ZSS after being infested by P. interpunctella. Conclusions: The study provided the basis and reference for the identification of insect-infested ZSS and offered an example for the identification of other insect-infested edible and medicinal materials.